2009
DOI: 10.1111/j.1744-9987.2009.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Cinacalcet Replace Parathyroid Intervention in Severe Secondary Hyperparathyroidism?

Abstract: A 6-month observational study was conducted in 61 patients (33 men and 28 women, mean age 54.8 Ϯ 12.4 years) treated with cinacalcet in whom parathyroid intervention was indicated. Thirty-seven patients had baseline intact parathyroid hormone (iPTH) levels of >500 pg/mL, but only five still had levels this high after 6-month cinacalcet therapy. No patients had phosphorus (P), calcium (Ca), or iPTH levels within the target range at baseline, but six patients (9.8%) reached all three target ranges after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Conversely, other authors (31,32) failed to detect significant morphological changes after cinacalcet therapy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Conversely, other authors (31,32) failed to detect significant morphological changes after cinacalcet therapy.…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, this study does not allow to determine whether a regression of PTG with DH is possible after cinacalcet therapy. Actually, this hypothesis has been first based on the data obtained in experimental studies (18,19,20,21,22,23) and then by the US evaluation of PTG (28,29,30,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In a 6-month observational study in Japan, cinacalcet prevented parathyroidectomy in 80% of patients who had indications for parathyroidectomy. 105 However, the indications for parathyroid intervention in this study of 61 patients were much more aggressive than guidelines practiced elsewhere. 105 Cinacalcet, by reducing PTH to 250 pg/mL in 48% of patients with PTH range of 500 to 800 pg/mL and in 20% of patients with 4800 pg/mL, eliminated indications for parathyroidectomy in Japanese patients.…”
Section: Cinacalcet and Bone Density Fractures And Parathyroidectomymentioning
confidence: 58%
“…105 However, the indications for parathyroid intervention in this study of 61 patients were much more aggressive than guidelines practiced elsewhere. 105 Cinacalcet, by reducing PTH to 250 pg/mL in 48% of patients with PTH range of 500 to 800 pg/mL and in 20% of patients with 4800 pg/mL, eliminated indications for parathyroidectomy in Japanese patients. 106 Therefore, the marked PTH-lowering effects of cinacalcet are sometimes referred to as ''medical parathyroidectomy.''…”
Section: Cinacalcet and Bone Density Fractures And Parathyroidectomymentioning
confidence: 58%
“…24 Several studies have shown the efficacy of cinacalcet for dialysis patients with secondary hyperparathyroidism refractory to treatment with active vitamin D derivatives and those with marked parathyroid hyperplasia, in whom surgical PTx may be the treatment of choice. 32, 33 Indeed, a post-hoc analysis of randomized clinical trials reported significant reductions in PTx in patients treated with cinacalcet compared with the placebo plus standard of care group. 34 Thus, indications for PTx and cinacalcet treatment overlap significantly.…”
Section: Assessment and Management Of Parathyroid Functionmentioning
confidence: 99%